Neurobiology and changing ecosystems: Toward understanding the impact of anthropogenic influences on neurons and circuits - Michaiel, Angie M.; Bernard, Amy (Frontiers in Neural Circuits, 2022)
Rapid anthropogenic environmental changes, including changing ecosystems due to habitat contamination, degradation, and climate change, have far-reaching effects on biological systems that may outpace animals’ adaptive responses (Radchuk et al., 2019). Nervous systems mediate interactions between animals and their environments and evolved over millions of years to detect and respond to environmental changes. The robustness of mechanisms that mediate adaptation at the cell and circuit level is not well understood. Behavioral changes from anthropogenic activity in individuals and populations are becoming increasingly well described, but the cellular, molecular, and circuit-level processes underlying those changes are profoundly underexplored. By extension, the field of neuroscience lacks basic predictive frameworks to describe which neurobiological processes may be resilient or vulnerable to changing ecosystems and/or which may lead to appropriate adaptation, migration to more suitable ecosystems, or attrition. In this perspective piece, preliminary evidence of anthropogenic environmental changes is explored. Selected mechanisms for modifying animal behavior and nervous system function in animals are presented, while highlighting an unmet need for rigorous scientific enquiry into the cellular, molecular, and circuit-level component processes underlying diverse responses to changing ecosystems.